SOCIAL MEDIA MANAGEMENT STRATEGIES FOR GLOBAL BRANDS ADVANCING RESPONSIBLE CONSUMPTION (SDG 12) (Lex localis - Journal of Local Self-Government, 2025)
The paper examines the use of social media considering the manner of how global brands are strategically implementing the concept of responsible consumption as suggested by Sustainable Development Goal 12 (SDG 12). The need that social media should serve as a significant component in the salience narrative communication is on the backdrop of the times in which the consumption decision depends more and more on the digital platform. The research will focus on the campaign, influencer collaboration/ interaction in any type on Instagram, twitter/x, YouTube, Linked in and tik Tok. This indicates that dialogue modes of communication through focus on two way communication and co-creation among audiences is more effective than one-way promotional messages in instilling consumer confidence and responsible consumption behaviors. Moreover, the presentation of the flexibility fostered by information, supplemented with impact campaigns also contribute to traffic and attention of the message by the audience at a considerable level as well. The research pursues the ongoing tussle especially when the brand communication does not recognize the reality situation in which the company conducts as comparing with the greenwashing charges. The difficulties act as a tool to foster the aura of authenticity, transparency and evidence-based communication in order to retain consumer trust. Moreover, the findings have demonstrated the need to harmonize the global congruency and regional communication, based on which a brand is supposed to model its strategies, without conflicting with the balance accompanying their fit into the global sustainability vowel. The analysis further suggests that social media have the potential of overcoming the scope of marketing channel so as not only becoming an evolutional site of consumer responsibility promotion but also, being a site of responsibility should tackling strategies with credibility, cultural sensitivity, and lay length commitment to sustainability.